2016
DOI: 10.1515/epoly-2016-0138
|View full text |Cite
|
Sign up to set email alerts
|

Polylactide/polycaprolactone asymmetric membranes for guided bone regeneration

Abstract: Abstract:The aim of this work was to develop bioresorbable, asymmetric membranes for guided bone regeneration (GBR). Two resorbable polymers -polylactide (PLA) and polycaprolactone (PCL) were used in fabrication process. Two different manufacturing methods were applied: electrospinning in the case of PLA and freeze-drying of PCL. Mechanical properties, stability in a water environment and biocompatibility of fabricated membranes were evaluated. Microstructure [scanning electron microscopy (SEM)] of the membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…This in vivo study showed no significant effect of pore size (10–200 µm) of PLA membrane on efficiency in treatment of diaphyseal defect in female rabbits ( ϕ 10 mm) within six months . Recent in vitro tests of the osteoblast‐like MG‐63 cell line performed on the porous PCL and PLA/PCL membranes (with pore diameters up to 30 μm) confirmed both biocompatibility and demonstrated that cells adhered well to the material surface of both types of membranes …”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…This in vivo study showed no significant effect of pore size (10–200 µm) of PLA membrane on efficiency in treatment of diaphyseal defect in female rabbits ( ϕ 10 mm) within six months . Recent in vitro tests of the osteoblast‐like MG‐63 cell line performed on the porous PCL and PLA/PCL membranes (with pore diameters up to 30 μm) confirmed both biocompatibility and demonstrated that cells adhered well to the material surface of both types of membranes …”
Section: Resultsmentioning
confidence: 85%
“…11 Recent in vitro tests of the osteoblast-like MG-63 cell line performed on the porous PCL and PLA/PCL membranes (with pore diameters up to 30 lm) confirmed both biocompatibility and demonstrated that cells adhered well to the material surface of both types of membranes. 12 Thermal Properties Namely, PLA and PCL form a partially miscible blend, whereby an amount of amorphous PCL is dissolved in the PLA-rich phase leading to a depression of the glass and melting temperature shift to lower values. 16 Reportedly, PCL serves as a nucleating agent to promote PLA crystallization when blended with PLA.…”
Section: Structural Propertiesmentioning
confidence: 99%
“…PCL, on the other hand, is semi-crystalline and elastic in nature; in addition to this, the processing temperature of PCL is also similar to the PLA and thus it is a perfect plasticizing agent for PLA not only in order to improve its elasticity but also to modulate its degradation rate (180)(181)(182). Pyzik and group (183) have prepared biodegradable and asymmetric membranes of PLA-PCL for guided bone regeneration. PLA matrix was prepared via electrospinning and PCL was fabricated using freeze drying method.…”
Section: Bps For Bone and Tissue Applicationsmentioning
confidence: 99%
“…Electrospinning is a simple, cost-effective and versatile method to prepare materials that mimic the native architecture of tissues. Electrospun scaffolds have attracted considerable interest in tissue engineering [ 21 ]. Moreover the possibility to modify the polymer solution used for electrospinning with bioactive substances or drugs make it an attractive method for nasal implant development.…”
Section: Introductionmentioning
confidence: 99%